Validity of both adenosine deaminase test and differential cell count for pleural tuberculosis diagnosis - Quiñones-Silva, Jhonatan Boris (2010)
Objective: To determine the validity of both adenosine diaminase (ADA) test and differential cell count for pleural tuberculosis diagnosis. Design: Retrospective study for diagnosis precision. Setting: Huacho Hospital, Ministerio de Salud, Huacho, Peru. Material: Medical records of patients with ADA test in pleural fluid. Interventions: Medical records study of patients with ADA test in pleural effusion performed from January 2005 through December 2007. ADA test values and differential cell counts were analyzed by ROC curve. Sensitivity (Se), specificity (Sp), predictive values (VPP and VPN) and likehood ratios (LRP and LRN) were found for each variable. Main outcome measures: ADA test cut-off point for pleural tuberculosis diagnosis. Results: Tuberculosis was responsible for most cases of pleural effusion; 47,5 UI/L was the cut-off point by ROC curve, with Se and Sp 73% and 90%, respectively (IC 95%: 0,74 - 0,95; p<0,001). The ROC curve for differential cell count cut-off point was 0,725, with Se and Sp 60,9 and 64,7, respectively (IC 95%: 0,47 - 0,79; p=0,129). Conclusions: The best cut-off point for pleural tuberculosis diagnosis was 47,5 UI/L. This test worked better to confirm the disease rather than ruling it out. Thus, a larger percentage of lymphocytes in the differential cell count (>72%) will increase the suspicious of pleural tuberculosis.